2018
DOI: 10.5424/sjar/2018161-11254
|View full text |Cite
|
Sign up to set email alerts
|

Do increasing prices affect food deprivation in the European Union?

Abstract: The rise of prices of agricultural commodities in global markets during 2007-2012 was followed by increased consumer food prices around the world. More expensive food may have an impact on consumer food access and thus on their welfare, not only in developing countries but also amongst the most vulnerable in developed countries. Using a longitudinal database from the Statistics on Income and Living Conditions and population-averaged models, we tested whether increasing food prices had an impact on household fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This observation was also confirmed by other studies (e.g., [62]), which asserted that providing CAP instruments for agriculture had a decisive influence on the increase in income in EU-12 countries and on a decrease in the disparities between the income of farmers and remuneration obtained in other occupations. Hence, agricultural policy is of key importance for reducing agricultural deprivation [63][64][65][66]. When it comes to the eco-efficiency thread, Grovermann et al [67] argued that innovative systems enabled by institutional help connected with production in agriculture increase overall efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…This observation was also confirmed by other studies (e.g., [62]), which asserted that providing CAP instruments for agriculture had a decisive influence on the increase in income in EU-12 countries and on a decrease in the disparities between the income of farmers and remuneration obtained in other occupations. Hence, agricultural policy is of key importance for reducing agricultural deprivation [63][64][65][66]. When it comes to the eco-efficiency thread, Grovermann et al [67] argued that innovative systems enabled by institutional help connected with production in agriculture increase overall efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…", which has a binary outcome (Yes/No). This indicator is used to capture food deprivation (García-Germán, Bardají and Garrido, 2018) or food insecurity in the EU (Loopstra et al, 2016). It has several advantages as a measure of food insecurity.…”
Section: Introductionmentioning
confidence: 99%
“…Agriculture is characterized by seasonality, the scale of risk and uncertainty resulting from weather conditions, variable work intensity and cyclicality of production which have destabilizing effects both on agricultural income and profitability of agricultural production [36,38]. This is also confirmed by the results of studies of other authors in which, on the example of various groups, it was shown that agricultural policy is of key importance for reducing agricultural deprivation [39][40][41][42]. Thanks to the CAP, this is also reflected in the EU, which is confirmed by the results of our analyzes.…”
Section: Agricultural Income Against the Non-agricultural Incomementioning
confidence: 84%